A Unique Case of Malignant Pleuropericardial Effusion: HHV-8-Unrelated PEL-Like Lymphoma—A Case Report and Review of the Literature - Farhan Mohammad; Muhammad Neaman Siddique; Faraz Siddiqui; M. Popalzai; Masoud Asgari; Marcel Odaimi (Case Reports in Oncological Medicine)
Primary effusion lymphoma (PEL) or body cavity lymphoma is a rare type of extra nodal lymphoma of B-cell origin that presents as lymphomatous effusion(s) without any nodal enlargement or tumor masses. It belongs to the group of AIDS related non-Hodgkin’s lymphomas. First described in 1996 in HIV infected individuals who were coinfected with Kaposi’s sarcoma-associated herpesvirus (KSHV) or HHV-8 virus, it was included as a separate entity in WHO classification of tumors of hematopoietic and lymphoid tissue in the year 2001. The definition included association with HHV-8 virus as a mandatory diagnostic criterion. However, cases were later reported where PEL-like disease process was diagnosed in HHV-8 negative patients. This was eventually recognized as a rare but distinct entity termed as “HHV-8-unrelated PEL-like lymphoma”. Herein, we are reporting a case of an elderly patient who presented with a large pleuropericardial effusion and was eventually diagnosed with this entity. Till date, only around 50 cases of HHV-8-unrelated PEL-like lymphoma have been reported and our case being EBV, HIV, and Hepatitis C negative makes it very unique and rare occurrence. We are also presenting a review of relevant literature focused mainly on comparing outcomes in patients treated with and without chemotherapy.